Scientific methods and cultural heritage an introduction to the application of materials science to archaeometry and conservation science - Artioli, Gilberto 1957- (Oxford University Press, 2010)
Artioli provides an introduction to the methods and rationales of the scientific investigation of cultural heritage materials, with an emphasis placed on the analytical strategies, modes of operation and resulting information rather than on technicalities.